Jade Chemicals, Inc. - Alegre, Bernardo R. (College of Engineering, 1965)
Capacity: 24 tons per 24-hour day -- Land area: 5242 sq. m. -- Fixed capital investment: 7,469,163 -- Operating cost at maximum production: 2,588,922 -- Sales at maximum production: 5,184,000 -- Pay-off time: 5-6 years -- Break-even point: 9.2 tons/day -- Shut-down point: 2.88 tons/day